2021
DOI: 10.1002/admi.202101646
|View full text |Cite
|
Sign up to set email alerts
|

Largely Improved Breakdown Strength and Discharge Efficiency of Layer‐Structured Nanocomposites by Filling with a Small Loading Fraction of 2D Zirconium Phosphate Nanosheets

Abstract: Dielectric film capacitors have aroused considerable attention on account of the fast development of pulsed power systems. However, enhanced energy density is always acquired at the cost of deteriorated charge/discharge efficiency. Herein, well balanced energy density and efficiency are achieved in a series of reasonably designed bilayer composites consisting of a ferroelectric layer and a paraelectric layer at the meantime. It is interesting to find that, when merely 1.6 wt% Zr(HPO4)2 nanosheets are introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Therefore, it can be concluded that the fabrics were well coated with the TiO 2 nanoparticles. These results are consistent with other studies on TiO 2 nanoparticles ( 29 , 33 37 ).…”
Section: Resultssupporting
confidence: 94%
“…Therefore, it can be concluded that the fabrics were well coated with the TiO 2 nanoparticles. These results are consistent with other studies on TiO 2 nanoparticles ( 29 , 33 37 ).…”
Section: Resultssupporting
confidence: 94%
“…This increase in E b can be linked to the following factors: (1) the interfaces between adjacent layers acting to prevent and delay the breakdown of charge carriers, thereby reducing charge migration, and (2) the applied voltage is mainly concentrated in the pure PEI layer with high breakdown strength. 38 The conductivities of the composites were also measured and are shown in Figure S2. The trilayer composites exhibit extremely low conductivity, indicative of their outstanding insulating performance.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly true for E b of the trilayer films that contain 0.2 wt % RGO@BTO nanosheets (610.8 kV/mm), approximately 143% of pure P­(VDF-HFP). This increase in E b can be linked to the following factors: (1) the interfaces between adjacent layers acting to prevent and delay the breakdown of charge carriers, thereby reducing charge migration, and (2) the applied voltage is mainly concentrated in the pure PEI layer with high breakdown strength . The conductivities of the composites were also measured and are shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 9 demonstrates the IR spectrum obtained from the DFT method and experimental analysis. A large peak was obtained in the 3100-3500 cm −1 range due to the stretch band between O-H and N-H [ 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. The peaks are the signals of OH, CH 2 , and C-O [ 74 , 75 , 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%